Culture, Change and Learning in Project-based Organizations - Idrobo Dávalos, Paul (2016)
Projects are the strategic means by which organizations implement their improvement initiatives, but not all are able to manage them in a way that ensures their performance. This article analyzes the impact of organizational culture, its adaptability to change and its learning capacity, as key elements for them to base their management on projects, while proposing good practices that increase their chances of success in this challenge.